Electrospun Bi₃⁺/TiO₂ nanofibers for concurrent photocatalytic H₂ and clean water production from glycerol under solar irradiation: a systematic study - Lee, Siew Siang (2022)
In this study, bismuth/titanium oxide (Bi3+/TiO2) composite nanofibers (herein after referred to as Bi/TiO2) with enhanced physicochemical properties thus photocatalytic efficiency are successfully synthesized via electrospinning which maximizes the uniformity of Bi and Ti at molecular level. Bi/TiO2 shows positive characterization through anatase crystallinity, large light utilization rate, high specific surface area and low electron holes pair recombination rate as a result of the novel materials synthesis approach. Glycerol as a typical pollutant of industrial wastewater, is used here to demonstrate the concurrent production of chean water and H2 over the well synthesized Bi/TiO2. Bi is incorporated to extend the light absorbance capability of TiO2 to visible light region. Experimental data shows that 3% Bi/TiO2 exhibits the highest H2 generation and Total Organic Carbon (TOC) removal. The reduction of TOC of 8% means the conversion of glycerol into H2 has been achieved, which is in favor of the production of clean water from highly polluted glycerol wastewater. An optimization study is undertaken by varying the calcination temperature to investigate properties-activity relationship of the new photocatalyst, which exhibited higher photocatlytic efficiency under both UV–visible and visible light compared with that of bare TiO2. The mechanism illustration is derived from the novel materials synthesis and property optimization to explain the rationale behind this interesting phenomenon. It is worth to note that Bi/TiO2 nanofibers represent a promising photocatalyst for environmental remediation and sustainability where it can be potentially used in glycerol by-product or waste from the industry under the renewable solar irradiation to generate H2 and clean water simultaneously.